Unmarried Sri Lankan youth: sexual behaviour and contraceptive use - Malith Kumarasinghe; W. Indralal De Silva; Ranjith de Silva; M. Suchira Suranga (BMC, 2022)
Plain Language Summary With early puberty and late marriage, Sri Lankan youth are more susceptible to unprotected and casual sex. The physical, psychological, and sociocultural impact of resulting pregnancies and Sexually Transmitted Diseases including HIV could be detrimental. In Sri Lanka, significant variation in sexual intercourse and concurrent use of contraceptive use was observed among different ethnic groups and sectors. Increased popularity for emergency contraceptive pills was observed among never-married female youth. Younger youth (teenagers) tend to engage in more unprotected sexual intercourse compared to older youth in Sri Lanka. Concentrating on reducing barriers to contractive access for younger youth in Sri Lanka is important. To prevent unwanted pregnancies, and Sexually Transmitted Diseases including HIV, targeted interventions are required especially for Tamil ethnic groups and estate sector youth populations in Sri Lanka.